Framework for Splitting Algorithm of NCAC-MAC Protocol for collision Avoidance in Wireless Ad Hoc Network (International Journal of Scientific Research and Management (IJSRM), 2015)
Ad Hoc Network used in military and emergency rescue environment. Co-operative communication effective technique to deal with the channel fading and improve network performance, and provides higher throughput and reliability. Ad Hoc Networks can connect different wireless devices to enable more powerful wireless applications and mobile computing capabilities. Co-operative approach promises improved throughput and delay performance. This work, proposed a network coding aware utility based relay selection strategies, to choose the best relay in an efficient and distributed manner. Also, MAC protocol enables co-operative relay transmission. Focus on the MAC layer protocol design which is critical to reap the performance gains brought from the physical layer. Use of NCAC-MAC protocol in wireless ad hoc networks increases the throughput and reduces delay. For avoiding collision in the network used the splitting algorithm to solve that problem in NCAC-MAC protocol for large size network. Using increases the throughput and reduce the delay over each network